Thrombocytopenia in Relation to Immune - Hematology - Figallo Moreno, Manuel Andrés (1962)
Since 1871 Bronn and Krause (4) observed an association between the presence purpuric syndrome and thrombocytopenia in peripheral blood. Idiopathic Thrombocytopenic Purpura in undoubtedly one of the most characteristic features is the purpuric syndrome and thrombocytopenia in peripheral blood. Any theory that tries to explain the pathogenesis of this disease have to give logical explanation to three fundamental aspects seen in this process. 1) Thrombocytopenia in peripheral blood. 2) normal or increased megakaryocytes in the bone marrow with morphological changes characteristic number. 3) Effect benefactor splenectomy in most cases.